Adalimumab for maintenance of remission in Crohn's disease - Cepek, Jeremy (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The objective of this review is to assess the efficacy and safety of adalimumab for maintenance of remission in patients with quiescent CD.